2020
DOI: 10.1016/j.cjtee.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between using cell phone and the risk of accident with motor vehicles: An analytical cross-sectional study

Abstract: Purpose Traffic accidents are one of the major health problems in the world, being the first cause of burden of illness and the second leading cause of death in Iran. The Sistan-Baluchestan province is one of the most accidental provinces of Iran with the highest rate of accidents-caused deaths. This study was conducted to determine the risk factors associated with traffic accidents in Zahedan through 2013 to 2016. Methods This analytical cross-sectional study was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The other findings in this study that most of the participants who used 500–1000cc motorcycles and unsafe riding behaviors had experienced of RTA. The current study adds to the evidence and reinforces previous research which concluded that average driving speed and bad driving safety behavior while driving are the human eror factors in the incidence of RTA's ( 7 , 8 , 27 , 36 ). In line with this study, adolescents who ride 500–1000cc motorcycles with an average driving speed of 60 km/hour; this is because adolescents have higher aggressive driving behavior ( 33 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The other findings in this study that most of the participants who used 500–1000cc motorcycles and unsafe riding behaviors had experienced of RTA. The current study adds to the evidence and reinforces previous research which concluded that average driving speed and bad driving safety behavior while driving are the human eror factors in the incidence of RTA's ( 7 , 8 , 27 , 36 ). In line with this study, adolescents who ride 500–1000cc motorcycles with an average driving speed of 60 km/hour; this is because adolescents have higher aggressive driving behavior ( 33 ).…”
Section: Discussionsupporting
confidence: 86%
“…This finding is in line with research conducted by National Highway Traffic Safety Administration (NHTSA) that 7% of deaths in accidents due to distraction while driving are adolescents aged 15–19 years ( 40 ), on other findings, it is more specific that driving distraction experienced by drivers. Adolescents can cause collisions, especially in female drivers ( 16 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, study done in Congo show that unfastening seat belts were seen to have 1.85 (±0.062) times odds of occurrence RTA-related fatality. 14 And study done in Iran show that using mobile phones during driving have 9.4 times higher chance of RTA than those not using mobile phones while driving. 15 In this study, routine practice of driving was in a range of less than 6 hours to 18 hours of driving per day and one fifth drove from 12-18 hours per day.…”
Section: Discussionmentioning
confidence: 96%
“…Apesar do uso de celular ser essencial como ferramenta de trabalho para os serviços de entregas, a utilização desse dispositivo ao dirigir limita a capacidade mental de processar e responder aos estímulos externos, 20 o que pode implicar no desvio da atenção do motorista ao ambiente externo, aumentando a tendência de acidentes. 21 A problemática em relação à utilização do celular também foi relatada no Irã, no qual um estudo evidenciou que, 21,9% dos motoristas na faixa etária de De acordo com a literatura o aumento dos acidentes com motocicletas também pode estar relacionado ao abuso de álcool durante a direção, visto que os altos níveis de álcool no sangue podem desencadear incoordenação motora, reduções na capacidade mental de percepção e raciocínio, 20,21 o que pode ocasionar mais acidentes.…”
Section: Methodsunclassified